2014
DOI: 10.18433/j3wp4f
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Anti-Tumor Necrosis Factor Therapies in Arthritis Patients

Abstract: Purpose. Inflammatory and rheumatic arthritis remain leading causes of disability worldwide. The arthritis therapeutic area commands the largest market for the prescription of biological and non-steroidal anti-inflammatory drugs (NSAID). Yet biotechnology and pharmaceutical companies conducting research and providing therapeutics in this area frequently face challenges in patient safety.  The purpose of our study was to assess safety of anti-tumor necrosis factor therapies in arthritis patients.  Methods: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 237 publications
(237 reference statements)
1
30
0
1
Order By: Relevance
“…Biologics based on anti-TNFα antibodies are widely used in humans for the treatment of autoimmune diseases and can lead to increased susceptibility to disease or reactivation of latent infections (Saraceno and Chimenti 2008; Mootoo et al. 2009; Nanau and Neuman 2014; Shi and Liu 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Biologics based on anti-TNFα antibodies are widely used in humans for the treatment of autoimmune diseases and can lead to increased susceptibility to disease or reactivation of latent infections (Saraceno and Chimenti 2008; Mootoo et al. 2009; Nanau and Neuman 2014; Shi and Liu 2014). …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, IL-1␤ blockade shows greater promise (18,19). However, IL-1␤ blockade using monoclonal antibodies is likely to suffer from immunosuppressive side effects observed with TNF blockers (23). Thus, other anti-inflammatory approaches should be investigated.…”
mentioning
confidence: 99%
“…A recently published systematic review about the safety of anti-TNF treatment in patients with rheumatoid arthritis showed that infections, particularly reactivation of latent tuberculosis or de novo tuberculosis, infusion reactions and abnormalities in hepatic liver enzymes are the most common side effects in patients treated with infliximab [53]. The main adverse effects of adalimumab were infections and infusion reactions.…”
Section: What Side Effects Have Been Described For Tnf Antagonists Used?mentioning
confidence: 99%